(Ré)générer les communs par la pratique physique du territoire, le cas de la Boucle noire à Charleroi - Michael Bianchi (Projets de Paysage)
In Charleroi, at the beginning of the 2000s, in this industrial city in decline the number of brownfields increased. These abandoned areas were colonised by human and non-human actors who gradually rebuilt worlds on the ruins of industry. What are the issues involved in such practices, and what are the links between this low-key regeneration of abandoned peripheries and the public development strategies of so-called post-industrial cities? Through a study of the Black Loop, an urban trail that runs through the industrial periphery of Charleroi, this article seeks to identify the way in which the creation of a trail contributes to the emergence of new spatial values and the inclusion of specific aspects pertaining to the common.